Atmospheric particulate matter (PM10) exposure-induced cell cycle arrest and apoptosis evasion through STAT3 activation via PKCζ and Src kinases in lung cells. (July 2016) - Reyes-Zárate, Elizabeth; Sánchez-Pérez, Yesennia; Gutiérrez-Ruiz, María Concepción; Chirino, Yolanda I.; Osornio-Vargas, Álvaro Román; Morales-Bárcenas, Rocío; Souza-Arroyo, Verónica; García-Cuellar, Claudia María
Abstract: Atmospheric particulate matter with aerodynamic diameter ≤10 μm (PM10 ) is a risk factor for the development of lung cancer, but cellular pathways are not completely understood. STAT3 is a p21 Waf1/Cip1 transcription factor and is associated with proliferation and cell survival and is upregulated in lung cancer. PM10 exposure induces p21 Waf1/Cip1 expression, which could be related to STAT3 activation. The aims of this work were to investigate whether STAT3 was activated on lung epithelial cells after PM10 exposure and to determine whether or not STAT3 could have an impact on cell cycle distribution and cell survival. Our results showed that PM10 induced STAT3 activation through Src and PKCζ kinases, and it is partially responsible for the p21 Waf1/Cip1 induction that was also observed. Moreover, PM10 induced G1-G0 cell cycle arrest. The inhibition of STAT3 phosphorylation prevented cell cycle arrest and triggered apoptosis. These results suggest that PM10 exposure might activate a survival pathway related to STAT3 activation, similar to what has been described as part of the immune system and apoptosis evasion during tumor promotion and development. Highlights: PM10 induces STAT3 phosphorylation at Y705 and S727 residues. STAT3 phosphorylation occurs through Src and PKCζ kinases. PM10 induces cell cycle arrest in the G0-G1 phase. STAT3 phosphorylation regulates p21 Waf1/Cip1 levels. PM10 induces mechanisms associated to cellular survival. Abstract : PM10 exposure induces STAT3 phosphorylation via Src and PKCζ kinases, which were associated with cell survival and evasion of apoptosis in lung epithelial cells.